Multiplex ligation reaction based on probe melting curve analysis: a pragmatic approach for the identification of 30 common Salmonella serovars - Le Zuo; Min Jiang; Yixiang Jiang; Xiaolu Shi; Yinghui Li; Yiman Lin; Yaqun Qiu; Yinhua Deng; Minxu Li; Zeren Lin; Yiqun Liao; Jianbin Xie; et al. (BMC, 2019)
Abstract Background While Salmonella serotyping is of paramount importance for the disease intervention of salmonellosis, a fast and easy-to-operate molecular serotyping solution remains elusive. We have developed a multiplex ligation reaction based on probe melting curve analysis (MLMA) for the identification of 30 common Salmonella serovars. Methods Serovar-specific primers and probes were designed based on a comparison of gene targets (wzx and wzy encoding for somatic antigen biosynthesis; fliC and fljB for flagellar antigens) from 5868 Salmonella genomes. The ssaR gene, a type III secretion system component, was included for the confirmation of Salmonella. Results All gene targets were detected and gave expected Tm values during assay evaluation. Cross reactions were not demonstrated between the 30 serovars (n = 211), or with an additional 120 serovars (n = 120) and other Enterobacteriaceae (n = 3). The limit of identification for all targets ranged from using 1.2 ng/μL to 1.56 ng/μL of DNA. The intra- and inter-assay standard deviations and the coefficients of variation were no more than 0.5 °C and less than 1% respectively, indicating high reproducibility. From consecutive outpatient stool samples (n = 3590) collected over a 10-month period at 11 sentinel hospitals in Shenzhen, China, we conducted a multicenter study using the traditional Salmonella identification workflow and the MLMA assay workflow in parallel. From Salmonella isolates (n = 496, 13.8%) derived by both workflows, total agreement (kappa = 1.0) between the MLMA assay and conventional serotyping was demonstrated. Conclusions With an assay time of 2.5 h, this simple assay has shown promising potential to provide rapid and high-throughput identification of Salmonella serovars for clinical and public health laboratories to facilitate timely surveillance of salmonellosis.